Regulatory Twist and Synergistic Role of Metabolic Coinducer- and Response Regulator-Mediated CbbR-cbbI Interactions in Rhodopseudomonas palustris CGA010 - Joshi, Gauri S; Zianni, Michael; Bobst, Cedric E; Tabita, F. Robert (Journal of Bacteriology, 2013)
Rhodopseudomonas palustris assimilates CO2 by the Calvin-Benson-Bassham (CBB) reductive pentose phosphate pathway. Most genes required for a functional CBB pathway are clustered into the cbbI and cbbII operons, with the cbbI operon subject to control by a LysR transcriptional activator, CbbR, encoded by cbbR, which is divergently transcribed from the cbbLS genes (encoding form I RubisCO) of the cbbI operon. Juxtaposed between the genes encoding CbbR and CbbLS are genes that encode a three-protein two-component system (CbbRRS system) that functions to modify the ability of CbbR to regulate cbbLS expression. Previous studies indicated that the response regulators, as well as various coinducers (effectors), specifically influence CbbR-promoter interactions. In the current study, it was shown via several experimental approaches that the response regulators and coinducers act synergistically on CbbR to influence cbbLS transcription. Synergistic effects on the formation of specific CbbR-DNA complexes were quantified using surface plasmon resonance (SPR) procedures. Gel mobility shift and DNA footprint analyses further indicated structural changes in the DNA arising from the presence of response regulators and coinducer molecules binding to CbbR. Based on previous studies, and especially emphasized by the current investigation, it is clear that protein complexes influence promoter activity and the cbbLS transcription machinery.